Vacchi's palatal organ: a widespread trait in Holocephali. Issue 4 (21st February 2018) - Finucci, B.; Gallus, L.; Amaroli, A.; Candiani, S.; Rottigni, M.; Masini, M. A.; Ferrando, S.
Abstract : A palatal organ, possibly used for food sorting and processing, has previously been identified among the vomerine toothplates of the chimaeroid Chimaera monstrosa . In this study, the palatal organ was described in six additional species, confirming it is a widespread trait among holocephalans. It is proposed that this palatal structure, which appears to differ in shape according to each chimaeroid's degree of durophagy and is not homologous to the palatal structure described in teleosts, be hereby referred to as Vacchi's organ.